Hakikat Materi Pendidikan Agama Islam: Substansi, Struktur, dan Sejarah Perkembangannya - Minhaji Minhaji; Moh. Sulthon Hayatullah Toyyib; Moh. Akmalis Sholihin (Civiliza Publishing, Indonesia., 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students who are faithful, pious, and have noble character in accordance with the goals of national education. The success of PAI implementation is greatly influenced by learning materials that not only serve as a means of transferring religious knowledge but also as a medium for internalizing Islamic values ​​in students' lives. However, PAI materials are often understood partially and tend to be normative, thus not fully able to meet the needs of contextual learning in the modern era. This article aims to describe the nature of Islamic Religious Education materials, the substance contained therein, their structure in the education system, and the history of their development. This study uses a library research approach by utilizing various relevant literature sources as primary data. The analysis was conducted through descriptive analysis techniques of various literature on Islamic Religious Education materials. The results of the study indicate that PAI materials are a set of teaching materials sourced from the Qur'an, Hadith, and the results of ijtihad of scholars compiled to shape students who are faithful, pious, and have noble character. The substance of Islamic Religious Education (PAI) material encompasses faith, sharia, morals, the Quran and Hadith, and the history of Islamic culture, all systematically structured and interconnected. The development of Islamic Religious Education (PAI) material has undergone dynamics since the time of the Prophet Muhammad (peace be upon him) to the modern era, influenced by social, political, cultural, and educational developments. Therefore, Islamic Religious Education (PAI) material must be understood as a holistic, integrative, and adaptive whole.